L’idéologie éducative Wayana-Apalaï : l’identité culturelle autochtone à l’épreuve de l’écosystème - Maurizio Alì (Nuevo mundo - Mundos Nuevos, 2016)
This text is an excerpt from the second part of the PhD thesis in anthropology "From family education to Republican schooling. Two case studies in French Guiana and French Polynesia", a research aimed to describe and compare family educational practices of two autochthonous communities of French Overseas : on a side the Wayana and Apalaï - which form a community living in the French Guiana rainforest, and on the other side the Enata, living in Hiva Oa, one of the Marquesas Islands, in French Polynesia. In this excerpt we describe the educational ideologies observed among the Wayana-Apalaï between 2010 and 2015 and their influence on local educational styles, training priorities and strategies of social success. The results of our fieldwork show that the dynamics of national and global integration have succeeded in transforming local educational ideologies - especially those linked to the Amazon ecosystem - by introducing new criteria of success and assigning a leading educative role to formal schooling.